2022
DOI: 10.1038/s41409-022-01827-y
|View full text |Cite
|
Sign up to set email alerts
|

Infectious complications after second allogeneic hematopoietic cell transplant in adult patients with hematological malignancies

Abstract: We conducted a retrospective review of the infectious complications and outcomes over a 2-year follow-up period of adult patients who received a second allogeneic hematopoietic cell transplant (2nd allo-HCT) during a five-year period at two cancer centers in Michigan. Sixty patients, of whom 44 (73%) had acute leukemia or myelodysplastic syndrome, were studied. The majority ( n = 37,62%) received a 2nd allo-HCT because of relapsed leukemia. Infection episodes after the 2nd allo-HCT total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Previous studies have also reported that Enterococcus spp. were the major causative pathogens after the second HSCT and that previous HSCT was a risk factor for BSI with Enterococcus spp., which is consistent with the results of the present study ( 1 , 2 , 25 ). The risk of enterococcal infection increases as the duration of neutropenia increases, and in the present study, the high number of CBTs (characterized by a prolonged period of neutropenia) may have contributed to this increase ( 6 , 25 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Previous studies have also reported that Enterococcus spp. were the major causative pathogens after the second HSCT and that previous HSCT was a risk factor for BSI with Enterococcus spp., which is consistent with the results of the present study ( 1 , 2 , 25 ). The risk of enterococcal infection increases as the duration of neutropenia increases, and in the present study, the high number of CBTs (characterized by a prolonged period of neutropenia) may have contributed to this increase ( 6 , 25 ).…”
Section: Discussionsupporting
confidence: 94%
“…A study of 37 second-HSCT recipients [including 25 (67.6%) patients who underwent the second HSCT for graft failure] also reported a higher cumulative incidence of pre-engraftment BSI (35.1%) after the second HSCT than after the first HSCT ( 2 ). In another study that included 60 second-HSCT recipients [including 16 (27%) patients who underwent the second HSCT for graft failure], most bacterial infections, including BSI, occurred during the pre-engraftment period ( 1 ). Previous reports have shown that the cumulative incidence of pre-engraftment BSI or BSI at day 30 after first allogeneic HSCT ranged from 1.7% to 34% (2-4, 18-20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation